Durability study on the interlaminar shear behavior of glass-fibre reinforced polypropylene (GFRPP) bars for marine applications. (26th September 2022) - Zhou, Ping; Li, Chenggao; Bai, Yanbo; Dong, Shaoce; Xian, Guijun; Vedernikov, Alexander; Akhatov, Iskander; Safonov, Alexander; Yue, Qingrui
Highlights: Water absorption of GFRPP bars included a Fick's diffusion and development of micro-voids and cracks. Water absorption capacity and long-term ILSS of GFRPP bars and thermoset composites were compared. Mechanical properties decreased owing to development of micro-voids and fractures and interface debonding. Long-term life prediction was conducted to provide an application guideline of GFRPP bar. Abstract: This paper presents an investigation into the use of newly pultruded glass-fibre reinforced polypropylene (GFRPP) bars as reinforcement in concrete structures for marine applications. This study conducted a comparative evaluation of the durability of GFRPP bars in distilled water (DW) and alkaline solutions (AS) and in simulated marine concrete environments by investigating their interlaminar shear strength (ILSS). It focused on evaluating the water absorption, mechanical, and microstructural properties of GFRPP bars subjected to hygrothermal environments. Thermogravimetric analysis (TGA) tests obtained the fiber, volume content of the GFRPP bars. GFRPP bars were immersed solutions at different conditions. Scanning Electron Microscopy (SEM) and Fourier Transform Infrared spectroscopy (FTIR) were performed to study the changes of the microstructural and in the chemical composition of the polypropylene (PP) matrix of the GFRPP bars. Based on Arrhenius acceleration theory, the prediction models of ILSS of GFRPP bars in five preset service regions and DW and AS service environments were established to obtain the service time when they completely degraded in each service region and environment. The results show that the water absorptions of the GFRPP bars immersed in water and alkaline solution were described by Fick's equation. Moreover, after 120-day immersion at 60 °C, the retention of the ILSS was 67.0 and 67.5 % in DW and AS, respectively. The hygrothermal environments accelerates the development of micro-voids and cracks generated during the pultrusion of GFRPP bars, which is the main reason for the degradation of the long-term mechanical properties, as well as fiber-resin debonding. Finally, the predicted service life in AS solutions is shorter than in DW, owing to the catastrophic effect of glass fiber etching and stripping on the mechanical properties of GFRPP bars.